2021
DOI: 10.1155/2021/6697790
|View full text |Cite
|
Sign up to set email alerts
|

The Formation Mechanism of Surface Landslide Disasters in the Mining Area under Different Slope Angles

Abstract: Slope stability analysis is important for the safe mining of mineral resources. The collapse of goafs in loess gullies can lead to natural disasters such as surface landslides. In this context, this study analyzes monitoring data obtained from surface observation in the Shendong mining area of the Hanjiawan coal mine based on the geological conditions therein. The monitoring results show that the working face experiences a starting period, an active period, and a declining period, from the start of mining to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The slip caused by mining in the gully area is closely related to the stability of the slope in the gully area [25]. Chi Mu et al have also confirmed that underground mining can cause landslides by analyzing the mechanism of landslide disaster [18]. In the loess gullies, the slope stability is usually evaluated with G in the following formula as an index of terrain mining conditions [18,26,27]…”
Section: Slope Stability Analysis 421 Slope Stability Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The slip caused by mining in the gully area is closely related to the stability of the slope in the gully area [25]. Chi Mu et al have also confirmed that underground mining can cause landslides by analyzing the mechanism of landslide disaster [18]. In the loess gullies, the slope stability is usually evaluated with G in the following formula as an index of terrain mining conditions [18,26,27]…”
Section: Slope Stability Analysis 421 Slope Stability Evaluationmentioning
confidence: 99%
“…Xinpeng Diao et al evaluated the building's damage in mountainous mining regions by combining the subsidence theory and slope stability analysis method [12]. Based on the slope stability analysis of loess gully collapse, Chi Mu et al provided a scientific basis for effective prevention and control of geological disasters in Shendong mining Area [18]. Xugang Lian et al analyzed the slope stability caused by longwall mining based on realtime monitoring with global navigation satellite systems (GNSS) [19].…”
Section: Introductionmentioning
confidence: 99%
“…The instability of the fault structure and the fragmentation of the surrounding rock will change the pressure step of the overlying rock, the stability of the masonry beam structure and the stress distribution of the surrounding rock, etc. [1][2][3][4]. The theories of structural modeling, destabilization criteria, energy transfer criteria, and stability control of surrounding rock for independent faults have been gradually improved.…”
Section: Introductionmentioning
confidence: 99%
“…The surface perilous rock mass in a mining area refers to the rock structure that is distributed on a steep slope or cliff at the surface of the mine. Under the action of external forces, such as natural conditions or mining engineering activities, perilous rock is in, or near, the limit of the equilibrium state in which cracks or structural planes develop [1][2][3][4][5]. As a result of the rapid development of China's construction sector, human engineering activities have increased rapidly in many southwest regions of China's mountains, and perilous rock collapse disasters often occur [6][7][8].…”
Section: Introductionmentioning
confidence: 99%